Visual essays for the construction of the bourgeois nuclear family model: paintings of family in the Spanish House of Bourbon - Vidal Rivas, Julián (Arenal. Revista de historia de las mujeres, 2012)
In this article we will explore the involvement of architecture and painting in the field of eighteenth-century Spanish Bourbon House and also in the context of family’s structural rebuild. The development and consolidation of the nuclear family’s visual model and the role of women as field of power operations, are essential for the structural institution of the bourgeois State.